IbM PEMBUATAN BATU ALAM BUATAN MENGGUNAKAN BAHAN BAKU TEMPURUNG, KARANG, PASIR DAN SEMEN - Mekar Ria Pangaribuan; Meilani Belladona (DHARMA RAFLESIA, 2018)
Due to the increasing price and the issue of nature conservation, using natural stone as a building material causes its own problems. The purpose of this activity is to alternate the natural stone material with synthetic materials so that the natural nuances still appear without disturbing the natural. Artifical raw materials used are coconut shell, reefs are widely obtained around their residence. Method of implementation: 1) Collection of  raw materials of  portland cement, coconut shell, coral and sand, 2) Manufacture of molding beggisting size 15cm x 30cm (22 pieces), 25cm x 40cm (19 pieces), and 10cm x 40cm (1 piece) with 2 cm of thickness, 3) Preparation  of mortar with 2 layer composition, layer A with ratio 2 portland cement: 1 coconut shell: 1 coral, and B with the ratio of  mixture 1 portland cemen: 2 sand and sufficient water, 4) Printing by filling the volume of the mold and allowing for 3 days, 5) Opening the mold begisting after casting 3 days, then soaking immersed for 3 days to get desired hardness, 6) Stripping the top layer  to get desired texture with an iron grinder, 7) Doing the drying for 1 day and 8) We recommend that teh natural stone is finished with spesial paint for natural stone. The results obtained from the activity are: 1) Obtain the production of artifical natural stone, 2) Perform stripping of the top layer to obtain natural artificial stone texture using 2 cm thick grinding machine, 3) Conducting product marketing.Keywords: brand natural stone, coral stone, and piece of coconut shell.